2020
DOI: 10.1093/mnras/staa160
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA survey of the SCUBA-2 cosmology legacy survey UKIDSS/UDS field: Dust attenuation in high-redshift Lyman-break galaxies

Abstract: We analyse 870µm Atacama Large Millimetre Array (ALMA) dust continuum detections of 41 canonically-selected z 3 Lyman-break galaxies (LBGs), as well as 209 ALMA-undetected LBGs, in follow-up of SCUBA-2 mapping of the UKIDSS Ultra Deep Survey (UDS) field. We find that our ALMA-bright LBGs lie significantly off the locally calibrated IRX-beta relation and tend to have relatively bluer rest-frame UV slopes (as parametrised by β), given their high values of the 'infrared excess' (IRX ≡ L IR /L UV ), relative to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 136 publications
(223 reference statements)
3
6
0
Order By: Relevance
“…When comparing to lower redshift observations at z ∼ 5 − 6, however, we find that our IRLF is more than an order of magnitude lower. Finally, our IRLF shows an interesting evolution with redshift, compared with the literature, not only in number density (as was previously shown in Koprowski et al (2020); Fujimoto et al (2023)), but also in L * . This could be due to our UV-selected sample being biased to bright sources and further study with a similar selection at different redshift should be carried out to confirm the possibility of evolution with L * .…”
Section: Schechter Function Fitssupporting
confidence: 86%
See 1 more Smart Citation
“…When comparing to lower redshift observations at z ∼ 5 − 6, however, we find that our IRLF is more than an order of magnitude lower. Finally, our IRLF shows an interesting evolution with redshift, compared with the literature, not only in number density (as was previously shown in Koprowski et al (2020); Fujimoto et al (2023)), but also in L * . This could be due to our UV-selected sample being biased to bright sources and further study with a similar selection at different redshift should be carried out to confirm the possibility of evolution with L * .…”
Section: Schechter Function Fitssupporting
confidence: 86%
“…Similarly, Wang et al (2019a) shows a decreasing SFRD (light purple area) with large uncertainty in the last bin at z ∼ 4 (dashed light purple area). Koprowski et al (2020) presented a constrained SFRD up to z ∼ 4 (purple area). REBELS results shows the presence of dust at z ∼ 7 even in UV-selected galaxies.…”
Section: What Irlf Is Needed To Reproduce Extreme Sfrd?mentioning
confidence: 99%
“…The constant starburst is considered as a convenient approximation in SED modelling, but it has a drawback in generating templates with representative intrinsic UV colours (no dust). Koprowski et al (2020) showed that a constant starburst creates spectral templates of different ages with similar intrinsic UV colours, being less sensitive to the life time of the burst (see also Calzetti 2001;Mao et al 2012). In Figure 2 we compare the spectral templates in two extreme cases: one an instantaneous starburst (or a single stellar population) and the other a constant starburst.…”
Section: Star Formation Historiesmentioning
confidence: 99%
“…One can see that by increasing age over 10 − 500 Myr, β0 changes dramatically from −2.4 to 2.2 for the instantaneous starburst, while β0 mildly increases from −2.7 to −2.3 for the constant starburst. This is because the galaxy population is constantly replenished by the youngest stellar populations that dominate the UV radiation and result in an approximately constant UV colour (Koprowski et al 2020;Calzetti et al 2021).…”
Section: Star Formation Historiesmentioning
confidence: 99%
See 1 more Smart Citation